Antibacterial and Antibiofilm Activities of Chlorogenic Acid Against Yersinia enterocolitica - Chen, Kun; Peng, Chuantao; Chi, Fang; Yu, Chundi; Yang, Qingli; Li, Zhaojie (Frontiers in Microbiology, 2022)
Nowadays, developing new and natural compounds with antibacterial activities from plants has become a promising approach to solve antibiotic resistance of pathogenic bacteria. Chlorogenic acid (CA), as a kind of phenolic acid existing in many plants, has been found to process multifunctional activities including antibacterial activity. Herein, the antibacterial and antibiofilm activities of CA against Yersinia enterocolitica (Y. enterocolitica) were tested for the first time, and its mechanism of action was investigated. It was demonstrated that CA could exert outstanding antibacterial activity against Y. enterocolitica. Biofilm susceptibility assays further indicated that CA could inhibit biofilm formation and decrease the established biofilm biomass of Y. enterocolitica. It was deduced that through binding to Y. enterocolitica, CA destroyed the cell membrane, increased the membrane permeability, and led to bacterial cell damage. In addition, the transcriptomic analysis revealed that CA could disorder many physiological pathways, mainly including the ones of antagonizing biofilms and increasing cell membrane permeability. Finally, the spiked assay showed that the growth of Y. enterocolitica in milk was significantly inhibited by CA. Taken together, CA, as an effective bactericidal effector with application potential, exerts antagonistic activity against Y. enterocolitica by mainly intervening biofilm formation and membrane permeability-related physiological pathways.